A Cu-mediated one-pot Michael addition/α-arylation strategy using a diaryliodonium salt: a direct and efficient approach to α-aryl-β-substituted cyclic ketone scaffolds. Issue 11 (5th January 2016) - Pan, Jin-Long; Chen, Tao; Zhang, Zhi-Qiang; Li, Yi-Fan; Zhang, Xiao-Ming; Zhang, Fu-Min
Abstract : The first Cu-mediated, one-pot Michael addition/α-arylation method for preparing α-aryl-β-substituted cyclic ketone scaffolds has been developed. Abstract : The direct and efficient construction of α-aryl-β-substituted cyclic ketone scaffolds has been achieved using a Cu-mediated one-pot Michael addition/α-arylation strategy. The reaction features easily available materials, broad substrate scope, moderate to good yield, and an excellent diastereoselectivity.